The Effect of Latitude Differences, Sunshine Periods, Solar Radiation Quantities and Air Temperatures on Solar Electricity Generation. - Ali Samet SARKIN; Taner DİNDAR (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
Electricity supply has gained importance with the increase of electricity demand in the world. The energy that the sun can accept forever provides great convenience for electricity generation. In regions where the sun's rays are steep, it is easier to generate electricity from the solar energy, whereas in regions where the sun's rays are horizontal, the electricity production from the solar energy remains at a lower level. In this study, Istanbul and Adana are compared in the northern and southern regions of Turkey. These two cities were examined for daily sunshine periods, daily and monthly radiation amounts. The effects of air temperatures and sunshine durations on the average radiation amounts have been investigated. The province of Adana has an annual total of 1568.49 kWh, whereas the province of Istanbul has a total of 1327 kWh radiation. When the annual sunshine periods are examined, it is 97.13 hours in Adana and 78.99 hours in Istanbul. It is seen that less electricity production can be done year round in Istanbul province and the hourly production is more than that in Adana when compared to sunrise times. When the average annual temperatures are examined, Adana province is 19 °C and Istanbul province is 13.8 °C. Although the province of Istanbul has a lower average temperature, it has been found that it has a higher yield than the province of Adana.